Analisa Proyek Sistem Informasi E-Banking Pada Semua Bank Di Indonesia - Jermy Marcel Parulian; Muhamad Ridwan Ramadan; Aresti Selviliani Dewi; Yunita; Riska Pauziah; Ricky Firmansyah (Prodi Sistem Informasi FST Universitas Jambi, 2022)
Abstract The security factor is a major issue in the development of E-Banking because like other activities such as on the internet, banking transactions on the internet are also prone to surveillance and misuse by irresponsible hands. The purpose of this research is to analyze the e-banking information system project, how innovative traits can be used as a variable to positively influence the use of online banking and at the same time reduce perceptions of risk. Perceptions of risk can be interpreted as an individual's assessment of his or her own tendency to the consequences of losses and gains that arise and the level of consequences. Innovative nature as an underlying tendency for consumers to adopt new products or ideas. This research is a case study of measuring the quality of internet banking services using the webqual model, namely by measuring customer perceptions of two banks - one national private bank and one state-owned bank, about the quality of internet banking services. Instrument reliability and validity The results of the reliability test showed that the research variables had cronbach's alpha ranging from 0.826 to 0.934. Keywords: E-Banking, Case Study, Information System, Project Analysis, Reliability